1921 N.C. Sess. Laws 105, Pub. Laws, ch. 5, §§ 1-2. - (:unkn) unknown (General Publisher, 1921)
Any person who, with intent to commit crime, breaks and enters, either by day or by night, any building, whether inhabited or not, and opens or attempts to open any vault, safe, or other secure place by use of nitro-glycerine, dynamite, gunpowder, or any other explosive, or acetylene torch, shall be deemed guilty of burglary with explosives
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME